(3ecGJHI Cgd GdcdOGjI GdHjVGAs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3JhcdJ Ydi ehdGfG hMOg GdefLR dYHOg GdEeGe GdgGOi hYOg Edi GdcOjI GdHjVG GdZGdHhf CgdgG SdGe Ydjce HMSf fjGJce s
(3BNQgG (B:s
(3aEfgG hGUdI Ydi jOc hGdhUGI HJQc GdEUZGA Edi TGYGJ GdChZGO aEfgG eMfI hGbYI HCgdgG hGdSdGe hcJH bGFe GdReGf HNWg hGdMeO dehdGfG hMOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B24s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDdas
Keywords: (3GdJhMjO hGdedd hGdfMds